Cardiovascular Computing-Methodologies and Clinical Applications - Golemati, Spyretta; Nikita, Konstantina S. (Series in BioEngineering, 2019)
This book provides a comprehensive guide to the state-of-the-art in cardiovascular computing and highlights novel directions and challenges in this constantly evolving multidisciplinary field. The topics covered span a wide range of methods and clinical applications of cardiovascular computing, including advanced technologies for the acquisition and analysis of signals and images, cardiovascular informatics, and mathematical and computational modeling.